Соціальна відповідальність бізнесу: поняття, типологія та чинники формування - Кузьмін, О. Є.; Станасюк, Н. С.; Уголькова, О. З.; Kuzmin, O. Ye.; Stanasyuk, N. S.; Ugolkova, O. Z. (Видавництво Львівської політехніки, 2021)
Проаналізовано підходи до визначення поняття “соціальна відповідальність”. Досліджено види соціальної відповідальності та її прояви. Зроблено висновок, що ініціативи корпоративної соціальної відповідальності ґрунтуються на чотирьох різних категоріях. Запропоновано розділити усі чинники, що впливають на формування та розвиток соціальної відповідальності компанії, на дві групи: чинники дії та чинники забезпечення. Охарактеризовано один із можливих варіантів процесу фінансово-економічного забезпечення соціальної відповідальності.

In the article the authors analyze the approaches to the definition of “social responsibility”. The paper substantiates the relevance of implementing the principles of corporate social responsibility. The authors study the types of social responsibility and its manifestations. It is concluded that corporate social responsibility initiatives are based on four different categories, namely ethical responsibility, philanthropic responsibility, environmental responsibility and economic responsibility. The implementation of the principles of economic responsibility is extremely important, because in this case, economic decisions are made, taking into account their overall impact on both society and business. Thus, economic responsibility can improve business operations by engaging in sustainable practices. It is proposed to divide all factors influencing the formation and development of social responsibility of the company into two groups: factors of action (tax system and public administration systems; government surcharges, subsidies, rewards, etc.; creation of special funds, savings, etc.; volunteering and private initiative; other factors) and factors of provision (development of investment activity; formation of mechanisms of motivation and stimulation of involvement in the decision of social problems; construction of effective management systems; introduction of public-private partnership). The group of factors of action influences both at the national and local levels. Provision factors are based on the intensification of investment activities, which is the basis for innovation, which in turn will provide additional cash flow and create a strong financial and economic base for the formation of social responsibility systems. The article describes one of the possible options for the process of financial and economic support of social responsibility. It is substantiated that the consideration of these factors by business entities in their activities will help increase social investment, improve the image of companies, increase their attractiveness as participants in the business environment.
Social responsibility of business: concepts, typology and formation factors
Keywords: соціальна відповідальність; бізнес; підприємства; чинники; процес; social responsibility; business; enterprises; factors; process; 332.012.2